Environmental Contamination due to Multidrug-resistant Acinetobacter baumannii surrounding Colonized or Infected Patients - Thom, Kerri A. (2011)
BACKGROUND: Multidrug-resistant Acinetobacter baumannii (MDR-AB) is an important nosocomial pathogen associated with significant morbidity and mortality. METHODS: We conducted a prospective cohort study of intensive care unit patients colonized or infected with MDR-AB at a tertiary-care hospital from October 2008 to January 2009. For each patient, 10 surfaces in the patient room were sampled and evaluated for the presence of A. baumannii. Pulsed-field gel electrophoresis (PFGE) was performed on all environmental isolates and a clinical isolate if available. RESULTS: 50 rooms were sampled; 48% (24/50) were positive at one or more environmental sites. Supply carts (10/50, 20%); floors (8/50, 16%); infusion pumps (7/50, 14%); and ventilator touch pads (5/44, 11.4%) were most commonly contaminated. Patients with a recent history of MDR-AB were no more likely to contaminate their environment than patients with a remote history (51% vs. 36%, p-value = 0.50). In 85% (17/20) of cases the environmental isolate was classified as genetically similar to the patient isolate. CONCLUSIONS: For patients with MDR-AB, the surrounding environment is frequently contaminated, even among patients with a remote history of MDR-AB. Surfaces often touched by healthcare workers during routine patient care are commonly contaminated and may be a source of nosocomial spread.